2020
DOI: 10.1038/s41392-020-00303-7
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase-3 like-protein-1 function and its role in diseases

Abstract: Non-enzymatic chitinase-3 like-protein-1 (CHI3L1) belongs to glycoside hydrolase family 18. It binds to chitin, heparin, and hyaluronic acid, and is regulated by extracellular matrix changes, cytokines, growth factors, drugs, and stress. CHI3L1 is synthesized and secreted by a multitude of cells including macrophages, neutrophils, synoviocytes, chondrocytes, fibroblast-like cells, smooth muscle cells, and tumor cells. It plays a major role in tissue injury, inflammation, tissue repair, and remodeling responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
310
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(323 citation statements)
references
References 291 publications
(446 reference statements)
10
310
1
2
Order By: Relevance
“…The WT C57BL/6 develop NAFLD/NASH like pathology on HFD in association with enhanced Chi3L1 gene expression levels which allowed us to access the role of this gene in the pathogenesis of insulin resistance. It will be important to examine the role of stellate cells that also have upregulated Chi3L1 protein expression on hepatocyte injury, insulin resistance and fibrosis as described [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WT C57BL/6 develop NAFLD/NASH like pathology on HFD in association with enhanced Chi3L1 gene expression levels which allowed us to access the role of this gene in the pathogenesis of insulin resistance. It will be important to examine the role of stellate cells that also have upregulated Chi3L1 protein expression on hepatocyte injury, insulin resistance and fibrosis as described [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The Chi3L1 gene is also involved in mediating inflammation, tissue remodeling, fat accumulation and cancer [12,[19][20][21]42]. Moreover, investigations have suggested that Chi3L1 serum levels correlate with tissue injury and the degree of hepatic fibrosis [52].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CHI3L1 binding to CD44v3 induces the activation of Erk, Akt, and β-catenin signaling pathways enhancing cancer metastasis 22 . In cell lines, CHI3L1 stimulation results in the phosphorylation of Erk1/2 23 and a recombinant CHI3L1 was reported to significantly enhance the proliferation of SW480 cells, through the activation of MAPK/Erk signaling pathway 24 . Overall, CHI3L1-induced MMP2 overexpression plays a crucial role in ECM regulation promoting cancer cell growth, proliferation, invasion, and metastasis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CHI3L1 binding to CD44v3 induced the activation of Erk, Akt, and β-catenin signaling pathway enhancing cancer metastasis 23 . In cell lines, CHI3L1 stimulation results in the phosphorylation of Erk1/2 24 and a recombinant CHI3L1 was reported to signi cantly enhance the proliferation of SW480 cells, through the activation of MAPK/Erk signaling pathway 25 . Overall, CHI3L1-induced MMP2 overexpressionplays a crucial role in ECM regulation promoting cancer cell growth, proliferation, invasion, and metastasis 25 .…”
Section: Chi3l1-related Pathwaysmentioning
confidence: 99%